Limiting access to lethal means: applying the social ecological model for firearm suicide prevention. (25th June 2018) - Allchin, Adelyn; Chaplin, Vicka; Horwitz, Joshua
Abstract : This paper outlines a novel application of the social ecological model (SEM) for firearm suicide prevention. It focuses on four levels of intervention (societal, relationship, community and individual) to reduce access to firearms, a practical contributor to the capacity to attempt suicide, from individuals when they are at an elevated risk for suicide. There is substantive research linking easy access to firearms with an increased risk of firearm suicide, and suicide prevention interventions that address access to lethal means are critical components of a comprehensive suicide prevention strategy. Potential interventions using the SEM framework include: at the policy level—extreme risk laws, voluntary self-prohibition policies and policies that reduce the availability of firearms; at the community level—gun shop projects; at the relationship level—lethal means safety counselling; and at the individual level—safer storage. Taken together with upstream interventions, such as increased access to mental health services and substance use treatment, a multilevel approach for suicide prevention that addresses access to firearms can save lives.